Attraction Relationship with Enhancement English Language Skills at TBM Rita Home Library - Ramadhan, Rafi; Sumantri, Muhammad Abyath Daffa; Yanto, Andri (Universitas Pendidikan Indonesia, 2024)
Ability Language English impact on relationships international, because countries will intertwine connection or cooperation with other countries, and languages English often used as tool communication in international forums. Mastery Language English become indicator ability someone who is fluent in language, communicates and argues, has power think strong and capable solve problem, intelligence emotional as well as characteristic leadership. Method research used in research This is method survey. Earl Babbie explains that method survey is one of from method observation which is the research data collected with use sampling technique. The sampling technique used For get samples in research This is convenience sampling or conventional sampling. The research results obtained showing that correlation connection between activities, facilities, etc collection with enhancement language English child own a number of correlation connection. Conclusions obtained state that children who visit the Rita Home Library aim For obtain enhancement ability Language English .